A Meta-analysis of Central Corneal Thickness Changes With Overnight Orthokeratology. Issue 2 (March 2016) - Li, Fang; Jiang, Zhi-Xin; Hao, Peng; Li, Xuan
Abstract : Objectives: To assess the change of central corneal thickness (CCT) in the treatment of orthokeratology in patients with myopia. Methods: A systematic search of all relevant studies published through April 2014 was conducted, and 95% confidence intervals (CI) of CCT change were calculated. Random or fixed-effects models were used according to heterogeneity. Publication bias of the articles was evaluated using funnel plots and Begg test. Results: A total of 10 studies with 239 patients (339 eyes) from clinical studies were included. Central corneal thickness reduced significantly from 1 day to 1 week by 5.73 μm (95% CI, 1.75–9.70 μm; P =0.005), and a significant mean reduction of 5.89 μm also occurred from 1 day to 1 month (95% CI, 3.50–8.29 μm; P <0.001). No significant reduction was found between 1 week and 1 month ( P =0.32). Conclusions: Our meta-analysis demonstrated that most reduction of CCT occurred during the first week and remained thinner for 1 month. Further randomized controlled trials with larger sample sizes, standardized outcome measurements, and different follow-up periods are warranted to find the precise change.